Measuring Patient Safety in Primary Care: The Development and Validation of the “Patient Reported Experiences and Outcomes of Safety in Primary Care” (PREOS-PC) - Ricci-Cabello, Ignacio (Ann Fam Med, 2016)
PURPOSE: We set out to develop and validate a patient-reported instrument for measuring experiences and outcomes related to patient safety in primary care. METHOD: The instrument was developed in a multistage process supported by an international expert panel and informed by a systematic review of instruments, a meta-synthesis of qualitative studies, 4 patient focus groups, 18 cognitive interviews, and a pilot study. The trial version of Patient Reported Experiences and Outcomes of Safety in Primary Care (PREOS-PC) covered 5 domains and 11 scales: practice activation (1 scale); patient activation (1 scale); experiences of patient safety events (1 scale); harm (6 scales); and general perceptions of patient safety (2 scales). The questionnaire was posted to 6,736 patients in 45 practices across England. We used “gold standard” psychometric methods to evaluate its acceptability, reliability, structural and construct validity, and ability to discriminate among practices. RESULTS: 1,244 completed questionnaires (18.5%) were returned. Median item-specific response rate was 91.3% (interquartile range 28.0%). No major ceiling or floor effects were observed. All 6 multi-item scales showed high internal consistency (Cronbach’s α 0.75–0.96). Factor analysis, correlation between scales, and known group analyses generally supported structural and construct validity. The scales demonstrated a heterogeneous ability to discriminate between practices. The final version of PREOS-PC consisted of 5 domains, 8 scales, and 58 items. CONCLUSIONS: PREOS-PC is a new multi-dimensional patient safety instrument for primary care developed with experts and patients. Initial testing shows its potential for use in primary care, and future developments will further address its use in actual clinical practice.